KARAKTERISTIK PENDERITA DIABETES MELLITUS TIPE 2 DENGAN KOMPLIKASI ULKUS KAKI DIABETIK YANG DIRAWAT INAP DI RUMAH SAKIT VITA INSANI PEMATANGSIANTAR TAHUN 2013-2016 - Isnawati Devega Sihaloho; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT According to data from Health Research Association (2013), the prevalence of DM in Indonesia 2,1%. The prevalence of DM in 2013 in North Sumatera 2,3%. The prevalence of DM in 2013 in Pematangsiantar 2,2%. Approximately 15% of individuals with DM will experience of foot ulcer with risk of amputation by 14-24%. The purpose of this research is to find out the characteristics of patients type 2 DM with complications diabetic foot ulcer who were hospitalized at Vita Insani Pematangsiantar Hospital Year 2013-2016. This study is descriptive with case series design. The population and sample were 120 patients. Statistic analysis using Chi-Square and Kruskal Wallis. The highest proportion of patients with type 2 DM with complications of diabetic foot ulcer in ≥50 years old group (84,2%), female (52,5%), Batak Toba (41,7%), Christian Protestant (61,7%), Senior High School (52,5%), housewives (31,7%), Pematangsiantar (56,7%), degree 4 (38,3%), while blood glucose levels ≥200 mg/dL (68,3%), did not conduct bacteriological examination (78,3%), surgical treatment therapy (55,8%), not own cost (69,2%), average length of stay 5 days, becoming outpatient (91,7%). The statictical test   resulted, there is no significant difference between the proportion of distribution of age based on degree of diabetic foot ulcers (p=0,554), sex based on degree of diabetic foot ulcers (p=0,720), blood glucose levels based on degree of diabetic foot ulcers (p=0,477), duration of treatment on average based on degree of diabetic foot ulcers (p=0,051). There is a        difference between the proportion of distribution of therapeutic treatment based on degree of diabetic foot ulcers (p=0,036). It’s suggested for Vita Insani Pematangsiantar Hospital to improve information for foot care and proper handling when the sores. It’s suggested for patients of type 2 DM      perform the recommended diet, regular exercise, consume medicine of DM, checking blood glucose regularly. The patients of type 2 DM with complication diabetic foot ulcer should to implement the above suggestions, do foot care, health care visit immediately if found injury in foot. Keywords :      Diabetic Foot Ulcer, Characteristic, Vita Insani Pematangsiantar Hospital